Media and education in contemporary society – the role of philosophy - Ćurko, Bruno; Zagorac, Ivana (2008)
Every part of human existence seems to be susceptible to the influence of globalization process. Educational systems as well as education in general are not exceptions. One negative consequence of this omnipresent and pervading trend will be emphasized, namely the role of media, which are mostly governed by influential multinational corporations, in shaping a specific consumerist worldview of a young generations. Results of a several researches of media influence will be presented leading to a key question of a paper – what is the role of philosophy in contemporary society, with special notion on education. It is argued that philosophy could represent a current alternative to manufacturing a new consumer. A need for establishing and strengthening the concept of philosophy for children, with main aim at development of critical thinking in children will be discussed. On the other hand, a philosophy for children is itself a product of a globalization process, emerging of which is reflecting a complex dynamics of a society we live in.
ENG